축소 모형을 활용한 선수 규칙파 중 수륙양용장갑차의 내항 성능 평가 - 허영민(Youngmin Heo); 전명준(Myungjun Jeon); 윤현규(Hyeon Kyu Yoon) (大韓造船學會 論文集, 2024)
In the present study, seakeeping performance for an amphibious vehicle in regular head waves was analyzed and evaluated experimentally and numerically. First, seakeeping tests were performed to confirm the vehicle's motion response of heave, pitch motion and vertical acceleration in restricted wavelength ratio conditions for a simplified vehicle shape. Numerical analyses were also conducted for a simplified vehicle shape to validate the numerical solver. To simulate the vehicle's motions, multi-degrees of freedom were calculated by a dynamic fluid-body interaction solver in STAR-CCM+. Comparison between numerical and experimental results was carried out for a simplified vehicle shape. Numerical results are in good agreement with experimental results. Second, numerical analyses were performed for a detailed vehicle shape considering seaway wavelength conditions. The seakeeping performance for an amphibious vehicle was evaluated by comparing with the existing ship's seakeeping performance standards.